(untitled) (Forum Penelitian Agro Ekonomi, 2021)
West Kalimantan is inhabited by multi-ethnicity communities, such as Dayak, Melayu, and Java. Dayak community is the major ethnic and spread out in West Kalimantan province. At present, Dayak community has many restricted accesses for specifically agricultural information and technology innovation. The objective of this article is to identify the role of Dayak community chief and their communication strategy for agricultural development. The method used in this article was literature review about Dayak culture and their development communication. Dayak community was initially dwelling in Kalimantan region with main occupation as dry land farmers. Strategies to improve accessibility of Dayak community on information and technology innovation are suggested as follows: (a) empowering the role of community chief as liaison person (contact person), (b) revitalizing mass media using radio and television with Dayak culture attributes, and (c) establishing small group communication by participatory communication within and outside the community.